Prevention of CMV/EBV reactivation by double-specific T cells in patients after allogeneic stem cell transplantation: results from the randomized phase I/IIa MULTIVIR-01 study - Gerbitz, Armin; Gary, Regina; Aigner, Michael; Moosmann, Andreas; Kremer, Anita; Schmid, Christoph; Hirschbuehl, Klaus; Wagner, Eva; Hauptrock, Beate; Teschner, Daniel; Roesler, Wolf; Spriewald, Bernd; et al. (Frontiers in Immunology, 2023)
Introduction Allogeneic stem cell transplantation is used to cure hematologic malignancies or deficiencies of the hematopoietic system. It is associated with severe immunodeficiency of the host early after transplant and therefore early reactivation of latent herpesviruses such as CMV and EBV within the first 100 days are frequent. Small studies and case series indicated that application of herpes virus specific T cells can control and prevent disease in this patient population. Methods We report the results of a randomized controlled multi centre phase I/IIa study (MULTIVIR-01) using a newly developed T cell product with specificity for CMV and EBV derived from the allogeneic stem cell grafts used for transplantation. The study aimed at prevention and preemptive treatment of both viruses in patients after allogeneic stem cell transplantation targeting first infusion on day +30. Primary endpoints were acute transfusion reaction and acute-graft versus-host-disease after infusion of activated T cells. Results Thirty-three patients were screened and 9 patients were treated with a total of 25 doses of the T cell product. We show that central manufacturing can be achieved successfully under study conditions and the product can be applied without major side effects. Overall survival, transplant related mortality, cumulative incidence of graft versus host disease and number of severe adverse events were not different between treatment and control groups. Expansion of CMV/EBV specific T cells was observed in a fraction of patients, but overall there was no difference in virus reactivation. Discussion Our study results indicate peptide stimulated epitope specific T cells derived from stem cell grafts can be administered safely for prevention and preemptive treatment of reactivation without evidence for induction of acute graft versus host disease. Clinical trial registration https://clinicaltrials.gov, identifier NCT02227641.